Implementasi Algoritme Mapping Dengan Backtracking Pada Mobile Robot Dalam Maze - Fikri Fauzan; Dahnial Syauqy; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Autonomous Mobile Robot is rife in many researches especially the Maze Wall Follower robot that can find its way out of a very complicated labyrinth. In this study the Robot Maze Wall Follower using Backtracking algorithm is to trace all possible paths in the maze and recognize each node that is passed so as not to repeat the path that has been passed. This prototype is built using several modules of Arduino Nano as its processing, Ultrasonic sensor, Photodiode sensor and L298N Driver Motor. Test results from measurement of wall distance using HC SR04 Ultrasonic sensor which is tested as much as 4 times with different distance obtained by the distance of sensor distance to wall the smaller also the level of accuracy of sensor, line reading done with 3 different color and every color is done 3 times the test result is just a black color that can't reflect light that can be read by the photodiode sensor. Testing the robot control system, the left turn of success reaches 50% at the right turn reaches 70% and when the turnaround only reaches 40%. After mapping the maze using the Backtracking algorithm all paths that have been passed by the robot will be marked, after all the lines have been robot so the robot will stop moving.